Vicsek fractal slot substrate integrated waveguide leaky wave antenna for X-band application. Issue 10 (3rd July 2018) - Chowdhury, Deblina; Pal, Manimala; Ghatak, Rowdra
Abstract: A substrate integrated waveguide based leaky wave antenna with Vicsek-cross fractal shaped slot is proposed. Vicsek cross fractal is used here to obtain wide band and compact structure for wideband applications in X-band. The proposed design achieves a wide impedance bandwidth of 1.98 GHz ranging from 8.96 to 10.94 GHz. A near identical pattern bandwidth with peak realized gain of 8.41dBi is achieved over the resonance frequency band of the proposed antenna. A prototype in X-band of the proposed design is examined and measured for verification.